Exploring the potential of using simulation games for engaging with sheep farmers about lameness recognition - Jones, Matt L.; Barnish, Maxwell S.; Hughes, Robert R.; Murray, Aimee K.; Mansour, Omid; Loni, Tiziana; Vickery, Holly M.; Evans, Myfanwy L.; Green, Laura; Verdezoto, Nervo (Frontiers in Veterinary Science, 2023)
Introduction: Computer simulation games are increasingly being used in agriculture as a promising tool to study, support and influence real-life farming practices. We explored the potential of using simulation games to engage with sheep farmers on the ongoing challenge of reducing lameness. Working with UK stakeholders, we developed a game in which players are challenged with identifying all the lame sheep in a simulated flock. Here, we evaluate the game’s potential to act as a tool to help assess, train and understand farmers’ ability to recognise the early signs of lameness. Methods: Participants in the UK were invited to play the game in an online study, sharing with us their in-game scores alongside information relating to their real-life farming experience, how they played the game, and feedback on the game. Mixed methods were used to analyse this information in order to evaluate the game. Quantitative analyses consisted of linear modelling to test for statistical relationships between participants’ in-game recall (% of the total number of lame sheep that were marked as lame), and the additional information they provided. Qualitative analyses of participants’ feedback on the game consisted of thematic analysis and a Likert Scale questionnaire to contextualise the quantitative results and identify additional insights from the study. Results: Quantitative analyses identified no relationships between participants’ (n = 63) recall scores and their real life farming experience, or the lameness signs they looked for when playing the game. The only relationship identified was a relationship between participants’ recall score and time spent playing the game. Qualitative analyses identified that participants did not find the game sufficiently realistic or engaging, though several enjoyed playing it and saw potential for future development. Qualitative analyses also identified several interesting and less-expected insights about real-life lameness recognition practices that participants shared after playing the game. Discussion: Simulation games have potential as a tool in livestock husbandry education and research, but achieving the desired levels of realism and/or engagingness may be an obstacle to realising this. Future research should explore this potential further, aided by larger budgets and closer collaboration with farmers, stockpeople and veterinarians.